Steel with high welding strength, preparation method of steel and steel part
By dispersing Ti2O3 nanoparticles in steel, using their ability to adsorb Mn atoms, the formation of MnS is suppressed during welding, and the problem of MnS precipitation in the welding heat-affected zone is solved, and the welding strength and toughness are improved.
Patent Information
- Application Number
- CN202411747979.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-11
AI Technical Summary
The problems of MnS precipitation in the welding heat-affected zone seriously affect the welding effect, and the prior art is difficult to fundamentally suppress the formation of MnS.
By dispersing Ti2O3 nanoparticles with a particle size of no more than 100 nm in the steel matrix, these nanoparticles grow into submicron-scale particles during the welding process, adsorbing a large number of Mn atoms, thereby reducing the concentration of Mn atoms and inhibiting the formation of MnS.
The welding strength of steel is significantly improved, toughness is improved, the formation of brittle phases is reduced, and the mechanical properties after welding are improved.
Smart Images

Figure CN119411014A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to steel materials, and in particular to improving the welding performance of steel materials. Background Art
[0002] The heat affected zone of steel is formed in a special local heating and cooling process, which has a fast heating rate, high heating temperature and a wide cooling rate range. The phase transformation process of the heat affected zone is carried out under local and stress-constrained conditions. The heat affected zone of welding will produce coarse grain size and brittle structure, causing local brittleness. The problem of heat affected embrittlement in welding has always been the focus of attention. MnS is a common inclusion in steel. During the welding process, MnS inclusions will be dissolved into the matrix and then precipitated in the heat affected zone during the cooling process. MnS not only induces crack initiation, but also accelerates crack propagation. Under the action of external load, the interface between MnS and the matrix is debonded, and the stress field near the interface has a superposition effect with the stress field at the tip of the main crack, and finally develops together with the main crack, thereby accelerating crack propagation. At the same time, MnS is also the cause of lamellar tearing in the heat affected zone. Therefore, MnS will seriously affect the welding effect.
[0003] Therefore, researchers have used various methods to control MnS inclusions in steel. For example, strictly controlling the Mn and S contents in steel to reduce the MnS content; using high-temperature heat treatment to control the size and morphology of MnS; using oxide metallurgy to form MxOy-MnS composite inclusions to improve the distribution and size of MnS. However, the above methods are still difficult to fundamentally inhibit the formation of MnS in the heat-affected zone. Summary of the invention
[0004] The embodiments of the present application provide a high welding strength steel material and a preparation method thereof, and a steel part to solve the technical problem of MnS precipitation in the welding heat affected zone.
[0005] In a first aspect, an embodiment of the present application provides a high welding strength steel material, the high welding strength steel material comprising:
[0006] Steel substrate;
[0007] The Ti2O3 nanoparticles dispersed in the steel matrix have a particle size of no more than 100 nm.
[0008] In some embodiments of the present application, the titanium content of the high welding strength steel is 0.04% to 0.06% by mass; and all the titanium in the high welding strength steel exists in the form of Ti2O3 nanoparticles.
[0009] In some embodiments of the present application, the high welding strength steel includes, in terms of mass percentage, 0.03% to 0.05% C, 0.3% to 0.5% Si, 1% to 1.2% Mn, 0.5% to 0.7% Cr, 0.04% to 0.06% Ni, 0.04% to 0.06% Nb, 0.04% to 0.06% Mo, and 0.04% to 0.06% Ti.
[0010] In a second aspect, an embodiment of the present application provides a method for preparing a high welding strength steel, the method comprising the following steps:
[0011] Smelting steel in a vacuum melting furnace to form molten steel;
[0012] Providing a plurality of titanium wires, and when the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continuously feeding the plurality of titanium wires into the molten steel from a plurality of points on the surface of the molten steel within a predetermined time;
[0013] After the titanium wire is completely consumed, the molten steel is added into a mold and cooled to obtain the high welding strength steel.
[0014] In some embodiments of the present application, the predetermined temperature is 1500-1700° C.; and / or,
[0015] The predetermined vacuum degree is 8-12Pa.
[0016] In some embodiments of the present application, the diameter of the titanium wire is 0.8-1.2 mm; and / or,
[0017] The titanium wire is fed into the molten steel at a rate of 4 to 6 cm / s; and / or,
[0018] The predetermined time is 25 to 35 seconds.
[0019] In some embodiments of the present application, the distance between any two titanium wires is not less than 10 cm.
[0020] In some embodiments of the present application, the mass ratio of the total consumption of the titanium wire to the molten steel is 1:1800-2700.
[0021] In some embodiments of the present application, the molten steel is added into a mold and cooled, and the cooling rate is 50-80° C. / h.
[0022] In a third aspect, an embodiment of the present application provides a steel part, which includes high welding strength steel connected by welding, and the high welding strength steel is the high welding strength steel described in any embodiment of the first aspect, or the high welding strength steel prepared by the method described in any embodiment of the second aspect.
[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0024] The high welding strength steel provided in the embodiment of the present application is distributed with Ti2O3 nanoparticles with a particle size of no more than 100 nm, so that during the welding process of the high welding strength steel, the Ti2O3 nanoparticles in the heat affected zone will grow into submicron Ti2O3 particles. The submicron Ti2O3 particles can adsorb a large number of Mn atoms, thereby reducing the concentration of Mn atoms in the heat affected zone and fundamentally inhibiting the formation of MnS. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0027] Figure 1 This is a scanning electron microscope image of the high welding strength steel obtained in Example 1;
[0028] Figure 2 The scanning electron microscope images of the welding heat affected zone of the high welding strength steel obtained in Example 1 and the welding heat affected zone of the steel obtained in the comparative example;
[0029] Figure 3 The scanning electron microscope and energy spectrum diagram of the welding heat affected zone of the high welding strength steel obtained in Example 1 and the welding heat affected zone of the steel obtained in the comparative example;
[0030] Figure 4 The following are crack analysis diagrams of the welding heat affected zone of the high welding strength steel obtained in Example 1 and the welding heat affected zone of the steel obtained in the comparative example. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0032] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0034] The precipitation of MnS during welding operation will seriously affect the welding effect, and the existing technology cannot fundamentally inhibit the precipitation of MnS in the welding heat affected zone.
[0035] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0036] In a first aspect, an embodiment of the present application provides a high welding strength steel material, the high welding strength steel material comprising:
[0037] Steel substrate;
[0038] The Ti2O3 nanoparticles dispersed in the steel matrix have a particle size of no more than 100 nm.
[0039] Mechanism of action during welding: During welding, the heat-affected zone of steel experiences high temperatures. At this time, the Ti2O3 nanoparticles originally dispersed in the steel matrix grow and transform into submicron Ti2O3 particles. These submicron particles have strong adsorption capacity and can adsorb a large number of Mn atoms. The concentration of Mn atoms is reduced: Due to the adsorption of Ti2O3 particles, the concentration of Mn atoms in the heat-affected zone is significantly reduced. Inhibition of the formation of MnS: MnS (manganese sulfide) is a brittle phase that is easily formed during welding and has an adverse effect on the welding strength and toughness of steel. By reducing the concentration of Mn atoms, the formation of MnS is fundamentally inhibited, thereby improving the welding strength of steel.
[0040] The high welding strength steel described in the present application is distributed with Ti2O3 nanoparticles with a particle size of no more than 100nm. During the welding process, the Ti2O3 nanoparticles in the heat-affected zone will continue to grow and increase in particle size. Since the initial particle size of the Ti2O3 nanoparticles is within 100nm, its particle size will only increase to the submicron level, that is, several hundred nanometers and no more than one micron, during the welding process. In traditional smelting steel, the particle size of Ti2O3 particles usually reaches several microns.
[0041] Due to the low particle size of submicron Ti2O3 particles in the heat affected zone, their surface curvature is high and the surface energy is high. In addition, the lattice parameters of MnTiO3 and Ti2O3 are very close, which makes it very easy for submicron Ti2O3 particles to adsorb Mn atoms.
[0042] Specifically, according to the Gibbs-Thomson formula, the solute concentration at the interface between particles and the matrix can be quantitatively described as follows:
[0043]
[0044] Where Cr is the solute concentration at the interface between the particle and the matrix, C∞ is the equilibrium concentration of the solute in the matrix, γ is the interfacial energy of the particle-matrix interface, Vm is the molar volume of the particle, R is the gas constant, T is the isothermal temperature, and r is the radius of the particle. It can be seen that the smaller the particle size, the higher the concentration of Mn atoms enriched in the rest of the matrix interface.
[0045] At the same time, there are many vacancies inside the submicron Ti2O3 particles, which makes it easy for Mn atoms to diffuse into the interior of the submicron Ti2O3 particles. In fact, it has been found through research (see the Examples section of this application) that the concentration of Mn atoms adsorbed inside the submicron Ti2O3 particles is higher than the concentration of Mn atoms adsorbed on the surface. Therefore, submicron Ti2O3 particles can adsorb a large amount of Mn atoms, thereby reducing the concentration of Mn atoms in the heat-affected zone and fundamentally inhibiting the formation of MnS.
[0046] In summary, the high welding strength steel described in the present application is distributed with Ti2O3 nanoparticles with a particle size of no more than 100 nm, so that during the welding process of the high welding strength steel, the Ti2O3 nanoparticles in the welding heat affected zone will grow into submicron Ti2O3 particles. The submicron Ti2O3 particles can adsorb a large number of Mn atoms, thereby reducing the concentration of Mn atoms in the heat affected zone and fundamentally inhibiting the formation of MnS.
[0047] In some embodiments of the present application, the titanium content of the high welding strength steel is 0.04% to 0.06% by mass; and all the titanium in the high welding strength steel exists in the form of Ti2O3 nanoparticles.
[0048] It is easy to understand that the beneficial effect of the above-mentioned content of titanium element is that it can form a sufficient number of Ti2O3 nanoparticles in the high welding strength steel, and then form a sufficient number of submicron Ti2O3 particles in the welding heat affected zone, thereby ensuring high welding strength; while it will not make the concentration of titanium element in the high welding strength steel too high, thereby causing the particle size of the Ti2O3 nanoparticles to be too large.
[0049] In some embodiments of the present application, the high welding strength steel includes, in terms of mass percentage, 0.03% to 0.05% C, 0.3% to 0.5% Si, 1% to 1.2% Mn, 0.5% to 0.7% Cr, 0.04% to 0.06% Ni, 0.04% to 0.06% Nb, 0.04% to 0.06% Mo, and 0.04% to 0.06% Ti.
[0050] In a second aspect, an embodiment of the present application provides a method for preparing a high welding strength steel, the method comprising the following steps:
[0051] S1: smelting steel in a vacuum melting furnace to form molten steel in the vacuum melting furnace;
[0052] S2: providing a plurality of titanium wires, and when the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continuously feeding the plurality of titanium wires into the molten steel from a plurality of points on the surface of the molten steel within a predetermined time;
[0053] S3: Adding the molten steel into a mold and cooling it to obtain the high welding strength steel.
[0054] In some embodiments of the present application, the predetermined temperature is 1500-1700° C.; and / or,
[0055] The predetermined vacuum degree is 8-12Pa.
[0056] As an example, the predetermined temperature may be 1500°C, 1550°C, 1600°C, 1650°C, or 1700°C.
[0057] It is easy to understand that the predetermined vacuum degree will affect the oxygen content in the molten steel, and further affect the formation of Ti2O3 nanoparticles. Therefore, the predetermined vacuum degree should be adapted to the amount of Ti element added to the molten steel.
[0058] As an example, the predetermined vacuum degree may be 8Pa, 9Pa, 10Pa, 11Pa, or 12Pa.
[0059] In some embodiments of the present application, the diameter of the titanium wire is 0.8-1.2 mm; and / or,
[0060] The titanium wire is fed into the molten steel at a rate of 4 to 6 cm / s; and / or,
[0061] The predetermined time is 25 to 35 seconds.
[0062] It is easy to understand that after the titanium wire is fed into the molten steel, it quickly melts at high temperature, and under the violent molecular thermal motion, the titanium atoms quickly diffuse into the molten steel around the titanium wire. The beneficial effect of the diameter of the titanium wire being no more than 1.2 mm is that the concentration of titanium atoms in the molten steel in the area around the titanium wire will not be too high, so that the particle size range of the Ti2O3 nanoparticles can be controlled within 100 nm. The beneficial effect of the diameter of the titanium wire being no less than 0.8 mm is that while ensuring that the particle size of the Ti2O3 nanoparticles is small enough, the number of titanium wires used is as small as possible, thereby reducing the complexity of the process, and the metal titanium wire has sufficient stiffness, so that it can be smoothly inserted into the molten steel at a rate of 4 to 6 cm / s.
[0063] As an example, the diameter of the titanium wire is 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, or 1.2 mm.
[0064] As an example, the titanium wire is fed into the molten steel at a rate of 4 cm / s, 4.5 cm / s, 5 cm / s, 5.5 cm / s, and 6 cm / s.
[0065] As an example, the predetermined time is 25s, 27s, 30s, 33s, or 35s.
[0066] In some embodiments of the present application, the distance between any two titanium wires is not less than 10 cm.
[0067] It is easy to understand that the beneficial effect of the distance between any two titanium wires being not less than 10 cm is that the titanium wires are distributed more dispersedly, preventing the local concentration of titanium atoms in the molten steel from being too high, so that the particle size range of the Ti2O3 nanoparticles can be controlled within 100 nm.
[0068] In some embodiments of the present application, the mass ratio of the total consumption of the titanium wire to the molten steel is 1:1800-2700.
[0069] It is easy to understand that, considering the burn-off of titanium during the smelting process, the mass ratio of the total consumption of the titanium wire to the molten steel is 1:1800-2700, which can make the titanium content in the high welding strength steel between 0.04% and 0.06%.
[0070] In some embodiments of the present application, the molten steel is added into a mold and cooled, and the cooling rate is 50-80° C. / h.
[0071] As an example, the cooling method is to place the mold filled with the molten steel at ambient temperature. Usually, the cooling rate at ambient temperature is between 50 and 80° C. / h.
[0072] In summary, the embodiment of the present application provides a method for preparing a high welding strength steel. By introducing Ti2O3 nanoparticles during the steel preparation process and ensuring that they are uniformly dispersed in the steel matrix, the high welding strength steel described in the present application can be prepared, which has the following advantages:
[0073] 1. Improve welding strength: By inhibiting the formation of MnS, the welding strength of steel is significantly improved.
[0074] 2. Improve toughness: Reducing the formation of brittle phase MnS helps to improve the toughness and impact resistance of steel.
[0075] 3. Broad application prospects: This steel can be used to manufacture steel parts that require high welding strength and toughness, such as bridges, buildings, machinery, etc.
[0076] In a third aspect, an embodiment of the present application provides a steel part, which includes high welding strength steel connected by welding, and the high welding strength steel is the high welding strength steel described in any embodiment of the first aspect, or the high welding strength steel prepared by the method described in any embodiment of the second aspect.
[0077] It is easy to understand that, due to the high welding strength of the high welding strength steel, the welding between the high welding strength steels in the steel parts is very strong. The steel parts made of the high welding strength steel provided in the embodiment of the present application not only have excellent welding performance, but also can maintain stable mechanical properties and chemical stability in various harsh environments, thereby extending the service life and improving safety.
[0078] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0079] Example 1
[0080] First, this embodiment provides a high welding strength steel material, and the high welding strength steel material comprises:
[0081] Steel substrate;
[0082] The Ti2O3 nanoparticles are dispersed in the steel matrix, and the particle size of the Ti2O3 nanoparticles is within 100 nm.
[0083] The mass percentage content of each element in the high welding strength steel is 0.04% C, 0.4% Si, 1.1% Mn, 0.6% Cr, 0.05% Ni, 0.05% Nb, 0.05% Mo, and 0.05% Ti.
[0084] Then, this embodiment also provides a method for preparing the high welding strength steel, the method comprising the following steps:
[0085] Sa: without adding titanium, smelting the steel in a vacuum melting furnace according to the element composition of the high welding strength steel, and forming molten steel in the vacuum melting furnace;
[0086] Sb: providing a plurality of titanium wires, and when the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continuously feeding the plurality of titanium wires into the molten steel from a plurality of points on the surface of the molten steel within a predetermined time;
[0087] Sc: After the titanium wire is completely consumed, the molten steel is added into a mold and cooled to obtain the high welding strength steel.
[0088] Wherein, the predetermined temperature is 1500°C, and the predetermined vacuum degree is 12Pa.
[0089] The diameter of the titanium wire is 0.8 mm, the speed at which the titanium wire is fed into the molten steel is 6 cm / s, the predetermined time is 25 s, and the distance between any two titanium wires is not less than 10 cm.
[0090] The molten steel is added into the mold for cooling, and the cooling method is to place the mold containing the molten steel at ambient temperature for natural cooling.
[0091] Example 2
[0092] First, this embodiment provides a high welding strength steel material, and the high welding strength steel material comprises:
[0093] Steel substrate;
[0094] The Ti2O3 nanoparticles are dispersed in the steel matrix, and the particle size of the Ti2O3 nanoparticles is within 100 nm.
[0095] The mass percentage content of each element in the high welding strength steel is 0.05% C, 0.3% Si, 1.2% Mn, 0.5% Cr, 0.06% Ni, 0.04% Nb, 0.06% Mo, and 0.04% Ti.
[0096] Then, this embodiment also provides a method for preparing the high welding strength steel, the method comprising the following steps:
[0097] Sa: without adding titanium, smelting the steel in a vacuum melting furnace according to the element composition of the high welding strength steel, and forming molten steel in the vacuum melting furnace;
[0098] Sb: providing a plurality of titanium wires, and when the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continuously feeding the plurality of titanium wires into the molten steel from a plurality of points on the surface of the molten steel within a predetermined time;
[0099] Sc: After the titanium wire is completely consumed, the molten steel is added into a mold and cooled to obtain the high welding strength steel.
[0100] Wherein, the predetermined temperature is 1700°C, and the predetermined vacuum degree is 8Pa.
[0101] The diameter of the titanium wire is 1.2 mm, the speed at which the titanium wire is fed into the molten steel is 4 cm / s, the predetermined time is 35 s, and the distance between any two titanium wires is not less than 10 cm.
[0102] The molten steel is added into the mold for cooling, and the cooling method is to place the mold containing the molten steel at ambient temperature for natural cooling.
[0103] Example 3
[0104] First, this embodiment provides a high welding strength steel material, and the high welding strength steel material comprises:
[0105] Steel substrate;
[0106] The Ti2O3 nanoparticles are dispersed in the steel matrix, and the particle size of the Ti2O3 nanoparticles is within 100 nm.
[0107] The mass percentage content of each element in the high welding strength steel is 0.03% C, 0.5% Si, 1% Mn, 0.7% Cr, 0.04% Ni, 0.06% Nb, 0.04% Mo, and 0.06% Ti.
[0108] Then, this embodiment also provides a method for preparing the high welding strength steel, the method comprising the following steps:
[0109] Sa: without adding titanium, smelting the steel in a vacuum melting furnace according to the element composition of the high welding strength steel, and forming molten steel in the vacuum melting furnace;
[0110] Sb: providing a plurality of titanium wires, and when the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continuously feeding the plurality of titanium wires into the molten steel from a plurality of points on the surface of the molten steel within a predetermined time;
[0111] Sc: After the titanium wire is completely consumed, the molten steel is added into a mold and cooled to obtain the high welding strength steel.
[0112] Wherein, the predetermined temperature is 1600° C., and the predetermined vacuum degree is 10 Pa.
[0113] The diameter of the titanium wire is 1 mm, the speed at which the titanium wire is fed into the molten steel is 5 cm / s, the predetermined time is 30 s, and the distance between any two titanium wires is not less than 10 cm.
[0114] The molten steel is added into the mold for cooling, and the cooling method is to place the mold containing the molten steel at ambient temperature for natural cooling.
[0115] Comparative Example
[0116] This comparative example provides a steel material, and the difference between this comparative example and Example 1 is that: the steel material does not contain Ti2O3 nanoparticles, and the steel material contains micron-sized Ti2O3 particles; the titanium element of the steel material is directly smelted into molten steel together with other metal elements, instead of adding titanium wire after the molten steel is formed.
[0117] The details are as follows:
[0118] First, this embodiment provides a steel material, the steel material comprising:
[0119] Steel substrate;
[0120] The micron-sized Ti2O3 particles are dispersed in the steel matrix, and the particle size of the micron-sized Ti2O3 particles is within 100 nm.
[0121] The mass percentage content of each element in the steel is 0.04% C, 0.4% Si, 1.1% Mn, 0.6% Cr, 0.05% Ni, 0.05% Nb, 0.05% Mo, and 0.05% Ti.
[0122] Then, this embodiment also provides a method for preparing the steel material, which comprises the following steps:
[0123] Sa: smelting the steel in a vacuum melting furnace according to the elemental composition of the steel, and forming molten steel in the vacuum melting furnace;
[0124] Sb: When the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continue smelting for a predetermined time;
[0125] Sc: The molten steel is added into a mold and cooled to obtain the steel material.
[0126] Wherein, the predetermined temperature is 1500°C, and the predetermined vacuum degree is 12Pa.
[0127] The diameter of the titanium wire is 0.8 mm, the speed at which the titanium wire is fed into the molten steel is 6 cm / s, the predetermined time is 25 s, and the distance between any two titanium wires is not less than 10 cm.
[0128] The molten steel is added into the mold for cooling, and the cooling method is to place the mold containing the molten steel at ambient temperature for natural cooling.
[0129] Related experiments and effect data:
[0130] The high welding strength steel obtained in Example 1 was observed by scanning electron microscope. The scanning electron microscope image obtained is as follows Figure 1 As shown. Figure 1 It can be seen that the high welding strength steel obtained in Example 1 contains Ti2O3 nanoparticles with a particle size of less than 100 nm.
[0131] The high welding strength steel obtained in Example 1 was subjected to welding. The steel obtained in the comparative example was subjected to welding. The welding heat affected zones formed by the welding operation in Example 1 and the comparative example were observed by scanning electron microscope. The scanning electron microscope images obtained are as follows: Figure 2 As shown. Figure 2 It can be seen that in the heat affected zone of the high welding strength steel described in Example 1, there are submicron Ti2O3 particles with a particle size of about 500nm. In the heat affected zone of the steel described in the comparative example, micron Ti2O3 particles with a particle size of 3-4μm are formed.
[0132] The welding heat affected zones formed by the welding operations of Example 1 and the comparative example were analyzed by scanning electron microscope and energy spectrometer. The scanning electron microscope and energy spectrum diagrams obtained are as follows: Figure 3 As shown, Figure 3 (a) shows the distribution of manganese in the radial direction of submicron Ti2O3 particles in the heat affected zone of the high welding strength steel obtained in Example 1. Specifically, Figure 3(a) The manganese content point value on the manganese content curve corresponding to the point on the light yellow line on the submicron Ti2O3 particle image above, that is, the manganese content value of the point; Figure 3 (b) shows the distribution of Ti, Mn and S in the micron-sized Ti2O3 particles in the heat affected zone of the steel obtained in the comparative example. Figure 3 (a) It can be seen that in the heat affected zone of the high welding strength steel described in Example 1, the submicron Ti2O3 particles contain a large amount of Mn elements, and the distribution of Mn elements shows the following pattern: from the center to the outer surface of the submicron Ti2O3 particles, the concentration of Mn atoms first increases and then decreases. That is, the concentration of Mn atoms adsorbed inside the submicron Ti2O3 particles is higher than that of Mn atoms adsorbed on the surface. No MnS is formed inside the submicron Ti2O3 particles. Figure 3 (b) It can be seen that in the welding heat affected zone of the steel described in the comparative example, the Mn and S elements are both located outside the Ti element. It can be seen that the micron-sized Ti2O3 particles are the nucleation points of MnS, which not only adsorb a large amount of Mn elements, but also adsorb a large amount of S elements, forming a Ti2O3-MnS composite inclusion.
[0133] The areas with cracks on the heat affected zones formed by the welding operations of Example 1 and the comparative example were observed by scanning electron microscope, wherein Figure 4 (a) Figure 4 (b) are images of the heat affected zone of welding of the comparative example. Figure 4 (c) Figure 4 (d) are images of the heat affected zone of welding of Example 1. Figure 4 (a) It can be seen that in the heat affected zone of the steel described in the comparative example, the interface between MnS and the matrix and between MnS and Ti2O3 all peeled off, resulting in the generation of cracks of varying degrees (i.e., the cracks shown in the figure). Figure 4 (b) It can be seen that the composite inclusion of Ti2O3-MnS forms a secondary crack at the front of the main crack. The formation of the secondary crack may have a causal relationship with the formation of the main crack. Figure 4 (c) It can be seen that in the welding heat affected zone of the high welding strength steel described in Example 1, although some Ti2O3 nanoparticles exist in the area with highly concentrated stress, no cracks are observed. Figure 4 In (d), cracks are formed around certain Ti2O3 nanoparticles in the welding heat affected zone of the high welding strength steel described in Example 1; however, it can be clearly observed that the formation of the cracks has nothing to do with the Ti2O3 nanoparticles. The Ti2O3 nanoparticles are not the source of the cracks, and the cracks originate from the steel matrix.
[0134] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0135] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described with "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single items (individual) or plural items (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively. The "number of parts" involved in this application, such as weight parts, mass parts, etc., represent the proportional relationship between each component. In the proportional relationship involved in the present application, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0136] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A high welding strength steel material, characterized in that: The high welding strength steel includes: Steel substrate; The Ti2O3 nanoparticles dispersed in the steel matrix have a particle size of no more than 100 nm.
2. The high welding strength steel material according to claim 1, characterized in that: Measured in percentage by mass, the content of titanium in the high welding strength steel is 0.04% to 0.06%; and all the titanium in the high welding strength steel exists in the form of Ti2O3 nanoparticles.
3. The high welding strength steel material according to claim 2, characterized in that: Measured in percentage by mass of the high welding strength steel, the high welding strength steel includes: 0.03% to 0.05% C, 0.3% to 0.5% Si, 1% to 1.2% Mn, 0.5% to 0.7% Cr, 0.04% to 0.06% Ni, 0.04% to 0.06% Nb, 0.04% to 0.06% Mo, and 0.04% to 0.06% Ti.
4. A method for preparing high welding strength steel, characterized in that: The method comprises the following steps: Smelting steel in a vacuum melting furnace to form molten steel; Providing a plurality of titanium wires, and when the molten steel reaches a predetermined temperature and the vacuum degree in the vacuum melting furnace reaches a predetermined degree, continuously feeding the plurality of titanium wires into the molten steel from a plurality of points on the surface of the molten steel within a predetermined time; After the titanium wire is completely consumed, the molten steel is added into a mold and cooled to obtain the high welding strength steel.
5. The method for preparing high welding strength steel according to claim 4, characterized in that: The predetermined temperature is 1500-1700° C.; and / or, The predetermined vacuum degree is 8-12Pa.
6. The method for preparing high welding strength steel according to claim 4, characterized in that: The diameter of the titanium wire is 0.8 to 1.2 mm; and / or, The titanium wire is fed into the molten steel at a rate of 4 to 6 cm / s; and / or, The predetermined time is 25 to 35 seconds.
7. The method for preparing high welding strength steel according to claim 4, characterized in that: The distance between any two titanium wires shall not be less than 10 cm.
8. The method for preparing high welding strength steel according to claim 4, characterized in that: The mass ratio of the total consumption of the titanium wire to the molten steel is 1:1800-2700.
9. The method for preparing high welding strength steel according to claim 4, characterized in that: The molten steel is added into a mold for cooling, and the cooling rate is 50-80° C. / h.
10. A steel part, characterized in that: The steel parts include high-welding strength steel connected by welding, and the high-welding strength steel is the high-welding strength steel described in any one of claims 1 to 3, or the high-welding strength steel prepared by the method described in any one of claims 4 to 9.